Dampak Pengembangan Desa Wisata Terhadap Aspek Ekonomi, Sosial Budaya dan Lingkungan di Alamendah Kabupaten Bandung - Anggi Maevawati; Emron Edison; Titing Kartika (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
The purpose of this study was to determine the impact of the development of a tourist village towards the aspect of economics, social culture, and physical environment in Alamendah. This study used descriptive qualitative approach. The data were collected by a researcher with direct observation, distribution of questionnaires, and interviews with the management of the Alamendah tourism village and the local community. The results showed that the development of the Alamendah tourism village had been carried out well, but in the attraction aspect there was still a lack of human resources, in terms of amenities, there was still a lack of hygiene & sanitation facilities, there were no supporting facilities for tourist safety and lack of cleaning facilities. In the Accessibility aspect, there is still a lack of directions to Alamendah Tourism Village. And there is still no control on ??the Ancillary aspect. The impact on the economic aspect has a significant positive impact but the income and standard of living of the community have a slight impact and the distribution of Public Infrastructure and Facilities has an impact but not significant. The impact on socio-cultural aspect has a significant positive impact, it's just that the erosion of the local language has already been felt by the community. The impact on environmental aspects has a significant negative impact. Such as polluted water sources due to the discharge of liquid and solid waste, decreased air quality due to air pollution and also noise pollution in Alamendah Tourism Village due to exhaust emissions from each vehicle and also noise generated from busy vehicles, damage to mountain vegetation and wild areas, as well starting from the change of residential land that turned into commercial land. However, Wildlife in Alamendah Tourism Village is still well preserved.